The Social Construction of “Good Boy” and “Good Girl” as Determinants of Toxic Productivity in Adolescents - Fransina Alfonsina Izaac; Natalia Paskawati Adimuntja; Dolfinus Yufu Bouway; Katarina Lodia Tuturop (FORIKES, 2026)
Fransina Alfonsina Izaac1, Natalia Paskawati Adimuntja1, Dolfinus Yufu Bouway1, Katarina Lodia Tuturop11Faculty of Public Health, Universitas Cendrawasih, Jayapura, IndonesiaCorrespondence: Fransina Alfonsina Izaac: Kampus Abepura, Universitas Cendrawasih, Abepura, Indonesia; fanyizaac87@gmail.com ABSTRACTAdolescents often internalize the labels “good boy” and “good girl” as indicators of obedience, achievement, and parental approval. These labels function as symbolic expectations that shape behavior, academic engagement, and daily routines. This study aimed to explore how the social construction of good boy and good girl labels influences adolescents’ productivity patterns and contributes to the emergence of toxic productivity among early adolescents in Jayapura. A qualitative phenomenological design was employed with eleven participants were selected through purposive sampling, consisting of six adolescents aged 10–13 years and five parents. Data were collected through participatory observation, in‑depth semi‑structured interviews, and documentation. All interviews were audio‑recorded, transcribed verbatim, and analyzed using thematic content analysis. Credibility was ensured through source triangulation between adolescents and parents. Three major themes emerged. First, overscheduling and externally driven activities: Adolescents participated in multiple extracurricular activities, computer courses, drawing, sports, church music, karate, and English classes often because “my parents told me to,” leading to fatigue and limited rest. Second, fake personality and conditional approval: Adolescents reported emotional pressure to maintain the good child image, often pretending to be obedient to avoid criticism or comparison. One participant stated, “Sometimes I pretend to be good so people will call me a good child.” Third, academic stress: High parental expectations and fear of disappointing adults led adolescents to associate academic performance with moral worth. Many expressed guilt and anxiety when unable to meet expectations, believing they must study “to achieve my parents’ dreams.” In conclusion, the social construction of good boy and good girl labels significantly shapes adolescents’ behavior, emotional experiences, and productivity patterns. These labels contribute to overscheduling, identity suppression, and heightened academic stress, collectively fostering toxic productivity in early adolescents.Keywords: good boy, good girl, toxic productivity, adolescents, parental expectations, academic stress, phenomenology